Human colonization of the Arctic the interaction between early migration and the paleoenvironment - Kotli︠a︡kov, V. M. (Vladimir Mikhaĭlovich); Velichko, A. A. (Andreĭ Alekseevich); Vasilʹev, S. A. (Sergeĭ Aleksandrovich) (Academic Press, 2017)
Human Colonization of the Arctic: The Interaction Between Early Migration and the Paleoenvironment explores the relationship between humans and the environment during this early time of colonization, utilizing analytical methods from both the social and natural sciences to develop a unique, interdisciplinary approach that gives the reader a much broader understanding of the interrelationship between humanity and the environment. As colonization of the polar region was intermittent and irregular, based on how early humans interacted with the land, this book provides a glance into how humans developed new ways to make the region more habitable. The book applies not only to the physical continents, but also the arctic waters. This is how humans succeeded in crossing the Bering Strait and water area between Canadian Arctic Islands. About 4500 years ago , humans reached the northern extremity of Greenland and were able to live through the months of polar nights by both adapting to, and making, changes in their environment.--Provided by publisher.